A Wide Spectrum Droplet Vitrification Cryopreservation Protocol for Conservation of Hops (Humulus lupulus) - Malhotra, Era; Mali, Suresh; Sharma, Shreya; Bansal, Sangita (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4): 292